Clachtoll An Iron Age Broch Settlement in Assynt, North-west Scotland - Cavers, Graeme (Oxbow Books, 2022)
Clachtoll broch is one of the most spectacular Iron Age settlements on the northern mainland of Scotland. When it became clear that the structure was threatened by coastal erosion, community heritage group Historic Assynt launched a major program of conservation and excavation works designed to secure the vulnerable structure and recover the archaeological evidence of its occupation and use. The resulting excavation provided evidence of a long and complex history of construction and rebuilding, with the final, middle Iron Age occupation phase ending in a catastrophic fire and collapse of the tower by the early years of the first century AD. The internal deposits span perhaps 50 years of the brochsquo;s final occupation and were remarkably well preserved, with no evidence for secondary re-use or disturbance after the fire. As a result, the excavation provides a remarkable snapshot of life in Iron Age Scotland, with an artifact assemblage attesting to daily agricultural life as well as long-range contacts that sets the broch within a wider Atlantic community. Specialist analysis of the artifactual and palaeoenvironmental evidence coupled with detailed analysis of the structure in its local geographical context combine to provide a major new contribution to the archaeology of north-west Scotland, with wider implications for our understanding of late prehistoric society in northern Britain.This report comprises the results of the archaeological investigations at Clachtoll, compiled by a team of archaeologists and specialists from AOC Archaeology Group, and brings together evidence from a range of specialist analyses as well as environmental and landscape investigations.